Author Correction: Metal-coordinated sub-10 nm membranes for water purification - You, Xinda; Wu, Hong; Zhang, Runnan; Su, Yanlei; Cao, Li; Yu, Qianqian; Yuan, Jinqiu; Xiao, Ke; He, Mingrui; Jiang, Zhongyi (Nature communications, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.An amendment to this paper has been published and can be accessed via a link at the top of the paper.